Hospital criminal liability as a corporation of patient rejection in infected with covid-19 - Handri Kristanto; Nyoman Serikat Putra Jaya (Legality : Jurnal Ilmiah Hukum, 2020)
One problem that has recently discussed is that there are hospitals that reject patients infected with COVID-19. COVID-19 has become a pandemic outbreak designated as a national disaster by the Government of Indonesia. Hospital administration in modern times is not as simple as it used to be. The need to manage hospitals with business principles is undeniable. Based on this paper, the research problem formulated is the criminal liability corporation of hospitals towards the rejection of patients infected with COVID-19. The method used in this research is normative juridical research (doctrinal research). The approaches used are case approach and statute approach. The outcomes indicate that based on Law Number 36 of 2009 concerning Health clearly said that hospitals are restricted to reject patients who need help. Hospitals as a corporation can be demanded criminally liable by using the doctrine of strict liability, namely criminal liability sans error. In this research, if the corporation that has committed a prohibited act as formulated in the law can already get sentenced without questioning whether the offender has an error (mens rea) or not.